The State of U.S. Railroads A Review of Capacity and Performance Data - Weatherford, Brian A. (RAND Corporation, 2008)
U.S. railroads have improved their productivity, but increasing freightvolume threatens performance-degrading capacity constraints. This reportdescribes the current state of railroad capacity and performance for freighttransportation. The public consequences of private investment decisionsjustify a public role in addressing concerns about railroads, but betterdata and analysis are needed to inform transportation policymaking.